170 USE OF BRAIN NATRIURETIC PEPTIDE IN THE DIAGNOSIS OF PATENT DUCTUS ARTERIOSUS IN PRETERM INFANTS. (1st January 2006) - Acherman, R. J.; Diaz, G.; Marquez, A.; Montealegre, A.; Ruiz, A.; Evans, W. N.; Mayman, G. A.; Cass, K. A.; Luna, C.F; Rothman, A.; Restrepo, H.
Abstract : Background: Brain natriuretic peptide (BNP) is a cardiac hormone released mainly by the cardiac ventricles in response to ventricular volume and/or pressure overload. BNP has been reported as a useful test in the diagnosis of patent ductus arteriosus (PDA) in premature newborns. Objectives: To evaluate the usefulness of determination of BNP serum levels in the diagnosis of PDA in a group of premature newborns. Methods: This study included 29 premature newborns (mean gestational age (GA): 31.6 ± 2.1 weeks) with PDA. The presence of a PDA was established by echocardiography (echo). Serum for BNP levels was collected at the time of echo. Patients were followed with serial echo until closure of the ductus was documented. Another blood sample for BNP was obtained with the last echo. Patients with heart disease other than PDA were not part of the study. BNP levels were also measured in 19 premature newborns without PDA (control group with a mean GA 32.0 ± 1.8 weeks and mean postnatal age of 2.7 ± 1.4 days). BNP levels were measured using a commercial kit (Triage® BNP Test Biosite Labs, San Diego CA). Results: There were 13 males and 16 females. Patients with a PDA had significantly higher mean BNP levels (858.5 ± 945.6 vs 105.9 ± 135.4 pg/mL, p = .002) than the control group at age of PDA diagnosis (2.8 ± 1.5 days vs 2.7 ± 1.4 days). There was no correlation between BNP levels and PDA diameter, pressure gradient across the PDA, left atrium/aorta ratio. The area under the receiver operator characteristic (ROC) curve for detection of PDA was 84% (95% confidence interval: 72%-95%). BNP level cutoff for diagnosis of PDA at 2.8 ± 1.5 days was 155.5 pg/mL (sensitivity: 75.9%, specificity: 83.3%, positive likelihood ratio: 4.5). Conclusions: The BNP test showed highly predictive diagnostic values. BNP levels were significantly higher in this group of premature infants with PDA.